Waves of magnetized plasma-filled waveguide with zero value of either of two transverse wavenumbers - Vatalii Shcherbinin (East European Journal of Physics, 2013)
This paper describes the electromagnetic properties of the waves in a magnetized plasma-filled waveguide with one transverse wavenumber being equal to zero. It was found, that despite zero denominators of the field expressions for such waves, the validity of these expressions is not violated. As a result it was shown that the wave frequency and field change continuously when one of its transverse wavenumbers crosses zero. It was also found, that the point of such crossing changes with the sign change of the wave azimuthal index.